Brides' Knowledge About Contraception In Preparation For Pregnancy - Renata, Dini; -, Machfudloh (Universitas Prima Indonesia, 2025)
Pregnancy is the period from conception to the birth of the baby, usually the normal length of pregnancy is 280 days or about 40 weeks / 9 months 7 days, therefore it is necessary to prepare for pregnancy for the mother-to-be. Low pregnancy preparation can result in pregnancy with complications, pregnancy with complications can increase morbidity and mortality for the mother and fetus. The National Population and Family Planning Agency (BKKBN) in 2020 also stated that the percentage of unwanted pregnancies in Indonesia in 2020 reached 17.5%, this occurred due to a lack of preparation before pregnancy and became one of the conditions that contributed to the Maternal Mortality Rate, recorded in 2020 which was 305 per 100,000 live births. The purpose of this literature is to find out how much knowledge the bride-to-be has about pregnancy preparation, especially knowledge about contraception. The search method is through Google Scholar and through a database in the form of PubMed, science direct, with inclusion criteria for publication years 2019 to 2024, discussing the knowledge of prospective brides about contraception and pregnancy, speaking Indonesian or foreign languages ​​and using original research. Out of a total of 1,180 articles, 10 articles were selected to be used for scoping reviews. Each article from a different country discusses the knowledge of brides-to-be regarding contraception, it can be concluded that the level of knowledge of brides-to-be regarding contraception gets a good category, even though the research is conducted in different countries.